Fourth Five Year Plan (1969-74) Annual Plan Programme for 1970-71 Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1969)
The proposals included in this publication relate only to the normal development programme to be under taken by this administration during 1970-71 and do not include the proposals under Accelerated Development Programme of the Ministry of labour, Employment and Rehabilitation (Department of Rehabilitation).
Andaman and Nicobar Administration